Fright Size - Twelve Ghost Plays. (2012) - Edgington, Jonathan; Bryant, Heather; Fitzsimmons, Karen; Nicholson, Gary; Reilly, Sarah; Donovan, Dian; Histed, Margaret; Spencer, Caroline; Dunn, David; Plumbley, Mike; Menary, Steve; 10 x 10 Writers,
No abstract available